Modulation of cerebral cortex activity by acupuncture combined with continuous theta-burst stimulation in post-stroke upper limb spasticity: an fNIRS study - Junfeng Zhang; Junfeng Zhang; Junfeng Zhang; Meng Wang; Hao Chen; Shiyu Fan; Shiyu Fan; Shiyu Fan; Rongshan Sun; Rongshan Sun; Rongshan Sun; Lin Wang; et al. (Frontiers in Neurology)
ObjectiveTo observe the modulation and clinical efficacy of acupuncture combined with continuous theta-burst stimulation (cTBS) on cerebral cortical activity in post-stroke upper limb spasticity.MethodsPatients with upper limb spasticity after stroke were randomly divided into two groups. The control group (n = 15) received acupuncture treatment, and the experimental group (n = 15) received cTBS treatment of the premotor cortex of the healthy side in addition to acupuncture. The efficacy was evaluated before and after the first treatment and 2 weeks after treatment. MAS, FMA, MBI, fNIRS and F wave evaluation were observed in the two groups.ResultsAfter treatment, there were significant differences between the two groups in MAS, FMA-UE, MBI, F-wave amplitude, and the F/M amplitude ratio index of the experimental group (p < 0.05). Comparison between groups, the MAS-elbow flexor in the experimental group decreased significantly after the first treatment and 2 weeks after treatment. After 2 weeks of treatment, the HbO2 concentration in the CH4 channel exercise phase in the experimental group increased compared with the control group (pFDR <0.05). The strength of functional connection in the left primary motor area (M1)—the left primary somatosensory cortex (S1), the left S1—the right premotor cortex and supplementary motor area (PMC & SMA), and the left S1—the left PMC&SMA showed an increasing trend (0.05 < pFDR < 0.1). The F wave amplitude was significantly lower than before intervention, and the difference was significant (p < 0.05).ConclusionAcupuncture combined with cTBS can relieve upper limb spasticity, enhance motor function, improve daily living ability, and reduce excessive spinal cord excitability. It can also increase HbO2 concentration in the cerebral cortex. However, large-sample studies are still needed to prove the effect of this therapy on brain networks.SignificanceThis study provides evidence for the potential of combined cTBS and acupuncture in stroke rehabilitation.Clinical trial registrationidentifier ChiCTR2400083631.